2005
DOI: 10.1093/humrep/deh724
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double-blind controlled study of the efficacy of laser-assisted hatching on implantation and pregnancy rates of frozen–thawed embryo transfer at the cleavage stage

Abstract: Laser AH did not improve the implantation rate of FET cycles and should not be performed routinely in all frozen-thawed embryos at the cleavage stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
53
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 30 publications
4
53
1
2
Order By: Relevance
“…However, to the best of our knowledge, no single study has been able to demonstrate sufficient evidence favourable to AH, and the current research conclusions are not unanimous (6)(7)(8)(9)(10)(11)(12)(13). In a large meta-analysis, Martins et al showed that laser-AH (LAH) is currently one of the best, safest and most effective AH methods (14).…”
Section: Introductionmentioning
confidence: 83%
“…However, to the best of our knowledge, no single study has been able to demonstrate sufficient evidence favourable to AH, and the current research conclusions are not unanimous (6)(7)(8)(9)(10)(11)(12)(13). In a large meta-analysis, Martins et al showed that laser-AH (LAH) is currently one of the best, safest and most effective AH methods (14).…”
Section: Introductionmentioning
confidence: 83%
“…Laser AH for frozen cleaved embryos is normally performed at the cleavage stage [3,6]. In this study, we performed laser AH for frozen cleaved embryos at the blastocyst stage.…”
Section: Discussionmentioning
confidence: 99%
“…assisted hatching (AH), may be useful for frozen thawed embryo transfer. However, very recent studies focused on the benefit of AH following frozen thawed embryo transfer reported controversial results with decreased [2], similar [3,4] or increased [5,6] implantation rates in the AH group compared to the control group. Different types of AH have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to all these reports, Sifer et al [24] indicated that the partial enzymatic digestion of ZP by pronase was not related to any benefit of the frozenthawed embryo transfer outcome, especially concerning the implantation ability of frozen-thawed embryos (N-AH, 9.6% vs AH, 9.2%) and clinical pregnancy (N-AH, 18.0% vs AH, 17.2%). In a study, Ng et al [25] found a negative effect of AH on frozen-thawed embryos. Matson et al [26] also suggested that cryopreservation of embryos is not associated with zona hardening or reducing implantation, making microdissection of the zona in such cases generally unwarranted.…”
Section: Discussionmentioning
confidence: 98%